On cocompact open set - Aziz Hussain Al-Abdulla, Raad; Hassan Jasim Al-Hussaini, Farah (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
In this paper, we have studied coc-continuous, coc-closed, coc-open functions and coc-compact space. We shall provided some properties of these concepts and it will explain the relationship among them and some results on this subjects are proved Throughout this work, some important and new concept have been illustrated including coc-compact, -space.